Development of hybrid exosome-mimetic nanoparticles for eye disease - Tan, Aaron Ming Hao (Nanyang Technological University, 2021)
Topical instillation is the most common route of ocular drug delivery due to its ease of administration and high patient compliance. However, with the complex structure and numerous barriers of the eye, the bioavailability of drugs administered topically is <5%. Thus, there is a need to introduce a new drug delivery system for ocular medications to overcome the low bioavailability. Cell-derived nanovesicles (CDNs) are exosome-mimetic vesicles with a superior production capability and possess membrane proteins that aid in cellular uptake. However, the CDNs exhibit a negative surface charge and would experience electrostatic repulsion to the corneal tissues. Consequently, the electrostatic repulsion would reduce the adsorption of the CDNs onto the corneal surface, affecting their cellular uptake and permeation. Thus, in this study, the aim was to hybridize CDNs with cationic materials to introduce a positive surface charge. This was done by centrifugal serial extrusion. Hybrid CDNs were synthesized using chitosan, polyallylamine hydrochloride (PAH), and dioleoyl-3-trimethylammonium propane (DOTAP). The hybrid CDNs were then characterized by nanoparticle tracking analysis and zeta potential (ZP), for hydrodynamic size and surface charge, respectively. The hybridization was shown to reduce the negative surface charge of the CDNs through the integration of cationic materials with the CDN membrane. DOTAP and PAH had shown good integration with CDNs, creating cationic hybrid CDNs with a zeta potential of 2.73 mV and 2.19 mV, respectively. Hence, DOTAP and PAH hybrid CDNs have the potential to be used as an ocular drug delivery system. Although chitosan had integrated with CDNs, the chitosan-hybrid CDNs failed to exhibit a positive ZP and were deemed unsuitable for this application.